ΒII‐Spectrin (SPTBN1) suppresses progression of hepatocellular carcinoma and Wnt signaling by regulation of Wnt inhibitor kallistatin. Issue 2 (February 2015) - Zhi, Xiuling; Lin, Ling; Yang, Shaoxian; Bhuvaneshwar, Krithika; Wang, Hongkun; Gusev, Yuriy; Lee, Mi‐Hye; Kallakury, Bhaskar; Shivapurkar, Narayan; Cahn, Katherine; Tian, Xuefei; Marshall, John L.; et al.
<x xml:space="preserve">Abstract</x> βII‐Spectrin (SPTBN1) is an adapter protein for Smad3/Smad4 complex formation during transforming growth factor beta (TGF‐β) signal transduction. Forty percent of SPTBN1+/− mice spontaneously develop hepatocellular carcinoma (HCC), and most cases of human HCC have significant reductions in SPTBN1 expression. In this study, we investigated the possible mechanisms by which loss of SPTBN1 may contribute to tumorigenesis. Livers of SPTBN1+/− mice, compared to wild‐type mouse livers, display a significant increase in epithelial cell adhesion molecule‐positive (EpCAM+) cells and overall EpCAM expression. Inhibition of SPTBN1 in human HCC cell lines increased the expression of stem cell markers EpCAM, Claudin7, and Oct4, as well as decreased E‐cadherin expression and increased expression of vimentin and c‐Myc, suggesting reversion of these cells to a less differentiated state. HCC cells with decreased SPTBN1 also demonstrate increased sphere formation, xenograft tumor development, and invasion. Here we investigate possible mechanisms by which SPTBN1 may influence the stem cell traits and aggressive behavior of HCC cell lines. We found that HCC cells with decreased SPTBN1 express much less of the Wnt inhibitor kallistatin and exhibit decreased β‐catenin phosphorylation and increased β‐catenin nuclear localization, indicating Wnt signaling activation. Restoration of kallistatin expression in these cells reversed the observed Wnt activation. Conclusion: SPTBN1 expression in human HCC tissues is positively correlated with E‐cadherin and kallistatin levels, and decreased SPTBN1 and kallistatin gene expression is associated with decreased relapse‐free survival. Our data suggest that loss of SPTBN1 activates Wnt signaling, which promotes acquisition of stem cell‐like features, and ultimately contributes to malignant tumor progression. (Hepatology 2015;61:598‐612)